Diseño de un prototipo de curvadora de perfiles metálicos para el taller metalmecánico FORM-ACERO. - Armijos Pineda, Armando Martin (2023)
The present project is about the design of a metal profile bending machine prototype for FORM-ACERO's metal mechanics to perform bending operations on structural elements up to 80 [mm] wide and 3 [mm] thick. The bending machine consists of a clamping and assembly system for the elements to be bent, the system is equipped with a pressure, and a start-up system. This project starts with gathering information about bending machine types and their most important features. The design of the bending machine was developed based on the design methodology where the technical specifications were determined according to the requirements and needs of the workshop. On the basis of a functional analysis, the modules and their respective functions were determined to propose alternative solutions and to be able to select the most optimal. To select the alternatives, a mechanical element was designed and the material selection to be used in the design process which was been carried out. The selection process of each mechanical element is also detailed and after that, a cost quantification is made for the bending machine. The design meets the established requirements and it is a contribution to FORM-ACERO metal mechanics, and to the development of the country's productive matrix. Key words: Profile bending machine, bending machine, metal, bending force